Isolation, Characterization and Identification of Bacteria from Industrial Waste Soil and Antibacterial Profile of Bacillus - Quratulain Ainee; Sayyada Ghufrana Nadeem; Sumaira Javed (RADS Journal of Biological Research & Applied Science, 2017)
Soil is a diverse environment in which different populations of microorganisms exist in different proportions. Soil facilitates the growth of many types of organisms as it contains a variety of nutrients that can be used as carbon source by microorganisms. Soil has the greatest capacity for accepting and decomposing pollutants of different kinds. Fifteen (15) different soil samples from industries of Karachi –Pakistan were collected and screened for their antibacterial activity. A standard procedure was employed for the isolation, identification and characterization of bacteria. Out of these samples, 7 different isolates of Bacillus, 4 different isolates of Staphylococcus, 2 different isolates of Pseudomonas, 1 isolates of Micrococcus and Serratia were isolated. Antibacterial activity was carried out using compound isolated from Bacillus. The compound was then isolated by centrifugation and assayed for its activity. The inhibitory activity of the Bacitracin was screened against E.coli, Pseudomonas aeruginosa and S.aureus. The research provides a step forward towards industrial development.